1995
DOI: 10.1080/01621459.1995.10476489
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Population Projection Errors for Census Tracts

Abstract: "In this article we evaluate the accuracy and bias of projections of total population and population by age group for census tracts in three counties in Florida. We use [U.S. census] data from 1970 and 1980 and several simple extrapolation techniques to produce projections for 1990; we then compare these projections with 1990 census counts and evaluate the differences. For the total sample, we find mean absolute errors of 17%-20% for the three most accurate techniques for projecting total population and find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 15 publications
2
47
0
Order By: Relevance
“…Second, there is considerable knowledge about the error in population forecasts for states and counties. For subcounty areas, this information is meager by comparison (e.g., Smith and Rayer 2010;Smith and Shahidullah 1995;Tayman 1996b;Tayman et al 1998) and greatly impedes the progress of understanding forecast uncertainty that relates directly to major and costly business, infrastructure, and policy decisions. Finally, presenting forecast uncertainty must have clear advantages; be cost-effective; be consistent with the agency mission and philosophy regarding the uses and roles of forecasting; and be understandable to management, stakeholders, and the general public.…”
Section: Discussionmentioning
confidence: 98%
“…Second, there is considerable knowledge about the error in population forecasts for states and counties. For subcounty areas, this information is meager by comparison (e.g., Smith and Rayer 2010;Smith and Shahidullah 1995;Tayman 1996b;Tayman et al 1998) and greatly impedes the progress of understanding forecast uncertainty that relates directly to major and costly business, infrastructure, and policy decisions. Finally, presenting forecast uncertainty must have clear advantages; be cost-effective; be consistent with the agency mission and philosophy regarding the uses and roles of forecasting; and be understandable to management, stakeholders, and the general public.…”
Section: Discussionmentioning
confidence: 98%
“…Also, these measures have been used by other researchers (Namboodiri 1972;Smith & Mandell 1984;Smith 1987;Smith & Shahidullah 1995). Mean absolute percentage error is the average error when only the magnitude of the error is considered.…”
Section: Discussionmentioning
confidence: 99%
“…In general, averaging methods improves accuracy of estimates (Smith et al 2002;Ahlburg 1999;Sanderson 1999;Smith & Shahidullah 1995;Long 1993;Byerly 1990;Lee 1989;Smith & Mandell 1984;Rosenberg 1968). California (Martindale 1999), Florida (Smith et al 2002) and Texas (Hoque & Murdock 1999) use averaging of population estimates from different methods to produce their county estimates.…”
Section: Introductionmentioning
confidence: 97%
“…In the demographic literature, there has been little interest in combining forecasts from different models. Nonetheless, some notable exceptions include Smith and Shahidullah (1995); Ahlburg (1998Ahlburg ( , 2001 and Sanderson (1998), whose pioneering work, particularly in the context of census tract forecast, have done much to awaken others, including the present author. The contribution of this article is to apply the notion of model averaging to the problem of forecasting age-specific life expectancies.…”
Section: Univariate Time-series Methodsmentioning
confidence: 99%
“…In the work by Smith and Shahidullah (1995), it was found that a forecast of census tract population based on simple average of forecasts from four extrapolation techniques 5 was as accurate as the single most accurate method. By combining forecasts from two methods that were found to predict accurately for particular types of tracts, they asserted that using knowledge of historical forecast performance can further reduce forecast error when combined.…”
Section: Univariate Time-series Methodsmentioning
confidence: 99%